3D Imaging of Tapetal Mitochondria Suggests the Importance of Mitochondrial Fission in Pollen Growth. Issue 2 (21st March 2019) - Chen, Pei-Ying; Wu, Chia-Chen; Lin, Chung-Chih; Jane, Wann-Neng; Suen, Der-Fen
Abstract : Mitochondrial fission is involved in regulating mitochondrial status in the tapetum and is critical for pollen development. Abstract: Mitochondrial fission occurs frequently in plant cells, but its biological significance is poorly understood because mutants specifically impaired in mitochondrial fission do not show obvious defects in vegetative growth. Here, we revealed that the production of viable pollen was reduced in mutants lacking one of the three main proteins involved in mitochondrial fission in Arabidopsis ( Arabidopsis thaliana ), DYNAMIN-RELATED PROTEIN3A (DRP3A)/Arabidopsis DYNAMIN-LIKE PROTEIN2A, DRP3B, and ELONGATED MITOCHONDRIA1 (ELM1). In drp3b and elm1, young microspores contained an abnormal number of nuclei, and mature pollen had aberrant accumulation of lipids in their coat and an irregular pollen outer wall. Because the formation of the pollen wall and coat is mainly associated with tapetal function, we used 3D imaging to quantify geometric and textural features of cells and mitochondria in the tapetum at different stages, using isolated single tapetal cells in which the in vivo morphology and volume of cells and mitochondria were preserved. Tapetal cells and their mitochondria changed in the volume and morphology at different developmental stages. Defective mitochondrial fission in the elm1 and drp3b mutants caused changes in mitochondrial status, including mitochondrial elongation, abnormal mitochondrial ultrastructure, a decrease in cross-sectional area, and a slight alteration of mitochondrial distribution, as well as a large reduction in mitochondrial density. Our studies suggest that mitochondrial fission is required for proper mitochondrial status in the tapetum and possibly in pollen as well and therefore plays an important role for the production of viable pollen.